Effect of Mergers and Acquisitions on Audit Fees and the Opinion of External Auditor: Applied Study on Jordanian Public Shareholding Companies - Bouqalieh, Bassam; Nour, Abdulnaser (Jordan Journal of Business Administration, 2019)
This study aims at showing the effect of merger and acquisition operations on Jordanian public shareholding companies by analyzing this effect on audit fees and on the company’s external auditor's opinion before and after mergers. The population and sample of the study consisted of all public shareholding companies listed in Amman Stock Exchange, which underwent the process of integration during the period (2009 - 2016). To achieve the objectives of the study, the researchers conducted descriptive statistics, correlation analysis, multiple regression analysis and non- parametric tests to test the study hypotheses in relation to the auditor's opinion. Parametric tests are used to test the hypotheses in relation to the auditor's fee; the McNamara test and the Pearson correlation matrix. The results of the study showed a positive effect of the merger process and the acquisition of audit fees, a positive effect of the ratio of receivables to total assets, size of the company and size of the audit office on audit fees, in addition to the absence of impact of return on assets and number of subsidiaries on audit fees. Based on the results of the study, several recommendations are proposed, the most significant of which is the encouragement of audit offices in Jordan to establish connections to international auditing offices, especially those which have expertise in mergers and acquisitions